алгебра 7 класс

Номер 697

 

Условие:

Решите уравнение:
а) (Зx - 1)(5x + 4) - 15x2 = 17;
б) (1 - 2х)(1 - 3х) = (6x - 1)х - 1;
в) 12 - х(х - 3) = (6 - х)(х + 2);
г) (х + 4)(х + 1) = х - (х - 2)(2 - х).

 

Ответ:

а) (3x - 1)(5x + 4) - 15x2 = 17 => 15x2 + 12x - 5x - 4 - 15x2 = 17 => 7x = 21 => x = 3;
б) (1 - 2х)(1 - 3х) = (6x - 1)х - 1 => 1 - 3x - 2x + 6x2 = 6x2 - x - 1 => 1 - 5x = -x - 1 => 4x = 2 => x = 0,5;
в) 12 - х(х - 3) = (6 - х)(х + 2) => 12 - x2 + 3x = 6x + 12 - x2 - 2x => 6x - 2x - 3x = 12 - 12 => x = 0;
г) (х + 4)(х + 1) = х - (х - 2)(2 - х) => x2 + х + 4х + 4 = x - 2х + x2 + 4 - 2х => х + 4х + 2x - х + 2х = 4 - 4 => х = 0.